Spin information transfer and transport in hybrid spinmechatronic structures - Karenowska, A; Gregg, J; Chumak, A; Serga, A; Hillebrands, B (2011)
Spin waves have long been recognized as potential signal carriers in spintronic devices. However, practical development of spin wave based information platforms is its infancy. To date, work in this area has focused on one-dimensional topologies based on purely magnetic thin-film transmission systems, typically exploiting interference phenomena to perform logical operations. In this paper, we describe an alternative approach in which spinmechatronic structures combining spin-wave transmission systems with magnetically loaded micro- and nano-mechanical elements provide spin-information processing functionality.